Cross‐modal symbolic processing can elicit either an N2 or a protracted N2/N400 response. (23rd March 2016) - Griffiths, Oren; Le Pelley, Mike E.; Jack, Bradley N.; Luque, David; Whitford, Thomas J.
Abstract: A cross‐modal symbolic paradigm was used to elicit EEG activity related to semantic incongruence. Twenty‐five undergraduate students viewed pairings of visual lexical cues (e.g., DOG) with congruent (50% of trials) or incongruent (50%) auditory nonlexical stimuli (animal vocalizations; e.g., sound of a dog woofing or a cat meowing). In one condition, many different pairs of congruent/incongruent stimuli were shown, whereas in a second condition only two pairs of stimuli were repeatedly shown. A typical N400‐like pattern of incongruence‐related activity (including activity in the N2 time window) was evident in the condition using many stimuli, whereas the incongruence‐related activity in the two‐stimuli condition was confined to differential N2‐like activity. A supplementary analysis excluded stimulus characteristics as the source of this differential activity between conditions. We found that a single individual performing a fixed task can demonstrate either a protracted N400‐like pattern of activity or a more temporally focused N2‐like pattern of activity in response to the same stimulus, which suggests that the N2 may be a precursor to the protracted N400 response.